66.3: Highly Improved Light Out‐coupling of the Organic Light‐Emitting Diodes by utilizing the Simple and Easy Process based Nano‐scale Random Light‐extraction Structure. Issue 1 (1st July 2013) - Park, Young Wook; Park, Tae Hyun; Song, Eun Ho; Shin, Se Joong; Kim, Hakkoo; Lee, Hyun Jun; Hwang, Ju Hyun; Choi, Kyung Bok; Ju, Byeong Kwon; Kim, Jung Suk; Lee, Kyu Back
Abstract: We report the highly efficient organic light‐emitting diodes (OLEDs) having the nano‐scale random light‐extraction structure (NsRLeS). The demonstrated NsRLeS realized the highly improved light out‐coupling, resulted improved electroluminescence efficiencies without introducing the spectral distortions at any viewing angles. The OLEDs having the developed light out‐coupling enhancement structure showed >90% improved power efficiency and >50% improved external quantum efficiency. The NsRLeS was fabricated by simple and easy process enough to apply on the mass production of the large scale OLEDs applications.